Effects Of Corporate Governance On Investment Efficiency And Firm Value: The Case Of Publicly Listed Companies In Gulf Cooperation Council (GCC) Countries - Gafeil, Adam Yahya (2022)
This study investigates the effect of corporate governance quality on investment efficiency and firm value in the six Arab Gulf countries, commonly known as Gulf Cooperation Council (GCC). The six member countries are United Arab Emirates, Bahrain, Kingdom of Saudi Arabia, Sultanate of Oman, Qatar, and Kuwait. first, the study developed a corporate governance quality model comprises 60 items under five main corporate governance elements of disclosure; responsibilities of the board; board effective composition; rights of shareholders and the role of stakeholders in corporate governance for each country. Secondly, the study examined the effect of corporate governance quality on investment efficiency and firm value. Investment efficiency as the dependent variable is measured by the deviation from firm’s expected level of investment, while firm’s value is measured by Tobin’s Q. Lastly, the study examined the impact of ownership concentration on the relationship between corporate governance quality and firm value. The study sample includes 301 publicly listed firms in the GCC countries for the period 2015-2020. Using multiple regression statistical analyses, the findings indicated that corporate governance quality levels vary by company.